Perioperative kardiovaskuläre Morbidität und Letalität bei nichtherzchirurgischen Eingriffen - Janßen, Henrike; Dehne, Sarah; Giannitsis, Evangelos; Weigand, Markus A.; Larmann, Jan (Der Anaesthesist, 2019)
Because of new surgical techniques, advanced monitoring modalities and improvements in perioperative care, perioperative mortality and morbidity have been significantly reduced in the last decades; however, patients still suffer from high perioperative mortality and morbidity, especially those with pre-existing cardiovascular diseases. Not only perioperative myocardial infarction but also myocardial injury after non-cardiac surgery, which presents without clinical symptoms, is associated with an adverse outcome. Patients at risk require particular interdisciplinary attention throughout the perioperative phase. The premedication visit is of particular importance. In addition to a thorough patient medical history and physical assessment, the perioperative handling of the patient’s pre-existing medication and possible necessity for further preoperative tests should be verified. If necessary and where possible, optimization of the patient’s state of health can be planned together with other disciplines. It is the anesthesiologist’s responsibility to optimally guide and support patients with pre-existing cardiovascular diseases through the entire surgical procedure. This review summarizes perioperative interventions that have an influence on patient mortality and morbidity and evaluates the underlying evidence. This covers the perioperative handling of cardioprotective medication, choice of the anesthetic regimen, blood pressure management and transfusion regimens. Furthermore, this review highlights recent findings, e.g. perioperative reloading with statins and short-term preoperative initiation of beta blockers. The pros and cons of thoracic epidural anesthesia in patients with an elevated cardiovascular risk are discussed. Not only intraoperative hypotension should be of concern to anesthesiologists but also postoperative hypotension can have a deleterious impact on the outcome. This is relevant in the time period when a significant proportion of patients have already left the monitoring ward. The recently published recommendations by the World Health Organization concerning perioperative hyperoxia might not be beneficial for patients with an elevated cardiovascular risk. Finally, the treatment options for perioperative cardiovascular events are explained and an algorithm for handling of patients with perioperative myocardial injury without clinical ischemic symptoms is suggested (myocardial injury after non-cardiac surgery).